Estudo da quiropterofauna (Mammalia: Chiroptera) de um fragmento urbano na cidade de Santarém, Oeste do Pará, Brasil - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2016)
Bats play a complex ecological role in regulating forest ecosystems, as they contribute to fundamental ecological services such as seed dispersal, pollination and insect populations controllers. The urban growth in biodiversity hotspots like Amazonia, constitute a risk factor to wildlife conservation, since the urbanization result in the natural landscape suppression. Several bat species adapt to urban habitat but the knowledge about the bat assemblages in the city. The present study aim to know the bat fauna from Tapajós Campus – Universidade Federal do Oeste do Pará, an urban area near the right bank of Tapajós river, in the Santarém Pará state, Brazil. With the sampling effort of 1440 m². h spreaded on twelve collect sessions between january to december 2015, were recorded 238 individuals of 13 species and five families: Phyllostomidae (n=198, 8sp), Vespertilionidae (n=8, 2sp), Noctilionidae (n=15, 1sp), Emballonuridae (n=7, 1sp) and Molossidae (n=10, 1sp). Among the 13 species recorded, Artibeus planirostris (n=173) was the dominant species representing 72,69% of the total captured individuals, followed by Noctilio albiventris (n=15, relative abundance of 6,3%), Molossus molossus (n=10), Rhinchonycteris naso and Eptesicus brasiliensis (n=7 each one). The bat fauna observed in the Tapajós Campus – UFOPA encompasses part of the local original assemblage (around 30%), that possibly resembled in the structure and composition with the surrounding natural areas, but became modified through the time by local species loss associated with landscape conversion due urbanization process. The bat fauna from Tapajós Campus remain as an important portion of the regional bat assemblages from lower Tapajós-Amazonas confluence having a high value in terms of biodiversity component to teaching/research, environmental education and conservation.
Keywords: Campus Tapajós; Morcegos; Biodiversidade; Conservação; CNPQ:: CIÊNCIAS BIOLÓGICAS